INCEIF deputy president Syed Othman retires - The Malaysian, Reserve (Themalaysianreserve, 2017)
INTERNATIONAL Centre for Education in Islamic Finance (INCEIF) deputy president academic Prof Datuk Dr Syed Othman Alhabshi has retired effective July 20, confirming an earlier report by The Malaysian Reserve.